Retrieving trends and issues of penyiaran/broadcasting in Malaysian Parliamentary Debates from 1957 to 2018: a culturomics approach - Jamaluddin Aziz, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The traditional concept of broadcasting is gradually becoming a misnomer due to technological transformations as epitomized by media convergence. Past studies on broadcasting in Malaysia often employed historical perspectives, policy analysis and technology impact frameworks. Thus far, no study has been carried out tracing Malaysian broadcasting issues over six decades. The knowledge of how penyiaran/broadcasting is debated in Parliament over time provides insights into the changing concerns in broadcasting throughout history in Malaysian context from the perspectives of the policy makers. The objectives of this research are to identify: 1) The frequency of the words penyiaran and broadcasting in Malaysian Hansard; 2) Patterns related to penyiaran/broadcasting in Malaysian Hansard; 2) Some issues as reflected by the patterns generated by the n-gram. This research employs both quantitative and qualitative approaches to analyze Malaysian Hansard Corpus (MHC) with about 157 million words from Parliament 1 (1959) to Parliament 13 (2018). Using AntConc software, culturomics is the quantitative approach that provides a tool to turn cultural patterns into empirical data. The pattern is generated in the form of an n-gram. The collocations retrieved help to identify the contexts of the issues and provide data for qualitative textual analysis. The main finding of this research is that the words penyiaran/broadcasting have lost its utility due to media convergence. The impact of the study is that it evokes ontological enquiry useful for media scholars, lawmakers and media practitioners to understand the changing conception of broadcasting so that more adaptive approaches and policies can be legislated.